Hasil Belajar Siswa SMK N 1 Pariaman melalui Metode Pembelajaran Project Based Learning Berbantuan Simurelay - Yendri; Mukhlidi Muskhir (Journal of Electrical Vocational Education, 2026)
This study was conducted due to the relatively low learning achievement of students in the Electric Motor Installation subject at SMK Negeri 1 Pariaman, especially in understanding wiring diagrams, recognizing control component functions, and applying electric motor control circuits. The purpose of this research was to examine the improvement of student learning outcomes through the application of the Project Based Learning (PjBL) model integrated with the Simurelay application. The research applied a pre-experimental method using a One-Group Pretest–Posttest Design. Participants involved in this study were 23 students from Class XI Electrical Power Installation Engineering (TITL) 2 at SMK Negeri 1 Pariaman. Data collection was carried out through pretest and posttest instruments, followed by analysis using the N-Gain Score and learning mastery evaluation. The results indicated that the average pretest score of students was 56.7, while the posttest average increased to 84.0. Furthermore, the N-Gain analysis produced a score of 0.7 with a percentage of 70.3%, which falls into the high category and reflects effective learning outcomes. Student learning mastery reached 82.6%, with 19 students successfully meeting the mastery criteria. Based on these results, the implementation of the Simurelay-assisted PjBL model was shown to be effective in improving student achievement in the Electric Motor Installation subject.